A mission oriented reconfiguration technology for Spaceborne FPGA. (April 2019) - Qin, J X; Yang, J; Qu, Z; Wang, Y X
Abstract: Reconfigurable technology based on FPGA is increasingly used in satellites to meet the demand of the increasing missions that satellites need to complete in recent years. In this paper, a mission oriented reconfiguration technology for spaceborne FPGA is introduced to address the problem that how to meet the demand of satellite reconfiguration mission to orbit, execution time and FPGA resource requirements. Satellite reconfiguration system is divided into three parts, that is, mission management module, reconfiguration management module and reconfigurable FPGA. Firstly, a mission list is set up to record the mission's execution time and space attributes, hardware space attributes and priority attributes. The mission is allocated to the FPGA resource area correspondingly based on the flexible region model. According to the time attribute and priority attribute of the mission, the reconfiguration management module carries out the reconfiguration action. And the reconfiguration management module mainly deals with reconfiguration library management and the entire or partial reconfiguration according to the configuration file. After the reconfigurable bit files are loaded to FPGA, the transformation and execution of the hardware resources from the mission to the hardware are completed. Finally, an evaluation of the real-time performance, reliability and security of the design is carried out. Experiments that based on a verification system composed of raspberry/PI and ZYNQ are conducted and results fully prove that the design in this paper can support mission oriented spaceborne FPGA reconfiguration.